EFFORTS TO INCREASE PATROLS BY SATSAMAPTA TO PREVENT MOTOR VEHICLE THEFT CRIMES IN THE JURISDICTION OF SEMARANG POLICE - DANDIKA ALHAQIQI (Indonesian Journal of Police Studies, 2022)
ABSTRACT EFFORTS TO INCREASE PATROLS BY SATSAMAPTA TO PREVENT MOTOR VEHICLE THEFT CRIMES IN THE JURISDICTION OF SEMARANG POLICE Dandika Sena Alhaqiqi, 18.193, senadandika@gmail.com The number of criminal cases of motor vehicle theft in the city of Semarang has increased from 2019 to 2021. This is due to the Covid-19 situation and condition, which actually cannot be said to be better than the conditions before Covid-19 because people's mobility is limited. This research focuses on the implementation of patrols and efforts to increase patrols by the Semarang Police Headquarters in preventing the crime of theft. The method used in this research is descriptive qualitative, which is reviewed with the concept of improvement efforts, the concept of patrol, the concept of Samapta, and the concept of the crime of theft. The theories used in this research are management theory (POAC and 6M), SWOT theory, and routine activity theory. Patrol implementation was analyzed using P-O-A-C management theory (Planning, Organizing, Actuating, and Controlling) and efforts to increase patrol were analyzed using The 6 M (Man, Money, Material, Methods, Machine and Market) management theory. The results obtained show that a number of obstacles are still found in patrol activities ranging from planning, organizing, implementing, and supervising patrols that are less than optimal and not in accordance with Perkabaharkam No. 1 of 2017. Factors that affect the implementation of patrols are analyzed using SWOT theory where there is a balance between strengths and the weakness of the Semarang Police Satsamapta in carrying out patrols. It can be concluded that the implementation of the Semarang Police Samapta Unit patrols in preventing theft has not been maximized due to the less optimal management process of patrol activities. The patrols carried out are still focused on the Covid-19 protocol so that the prevention of theft has not been maximally carried out by the Semarang Polrestabes Satsamapta. It is recommended for the Semarang Polrestabes Samapta Unit to improve and maximize the implementation of patrols by utilizing and maximizing human resources, budgets, materials, methods, machines, and patrol targets through new ideas and innovations, especially through the development of existing technology.